Efektivitas Gastroprotektif Rimpang Kunyit (Curcuma Domestica Val) Pada Lambung Yang Di Induksi Aspirin - Shelvia Athala (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Background: In the case of peptic ulcer, it is found mainly intermittent lesions and is most often diagnosed in middle-aged to elderly adults, but these lesions may have appeared from a young age which often occurs due to the use of non-steroidal anti-inflammatory drugs (NSAIDs). -selective, such as aspirin. Turmeric can protect the gastric mucosa by increasing mucus secretion and has a vasodilator effect so that turmeric can increase the gastric mucosal defense. Objective: to determine the effect of turmeric rhizome extract on gastric damage. Methods: Using literature studies from both national and international journals by summarizing the discussion topics and comparing the results presented in each article. Result: The essential oil contained in turmeric is efficacious to regulate the release of stomach acid so that it is not excessive. Turmeric is also thought to have analgesic activity because it contains curcuminoids and essential oils. Curcumin has an effect on COX-2 (cyclooxygenase2), nitric oxide synthesis, and biomarkers of the inflammatory response that will increase the production of macrophage cells from TNF- so that inflammation is reduced. Conclusion: administration of turmeric extract can stabilize the pH of gastric acid so that it can increase the healing rate of gastric ulcers. So that the turmeric rhizome has a protective effect on the stomach